Mesenchymal stromal cell‐derived factors promote the colonization of collagen 3D scaffolds with human skin cells. Issue 17 (14th July 2020) - Tutuianu, Raluca; Rosca, Ana‐Maria; Albu Kaya, Madalina Georgiana; Pruna, Vasile; Neagu, Tiberiu Paul; Lascar, Ioan; Simionescu, Maya; Titorencu, Irina
Abstract: The development of stem cell technology in combination with advances in biomaterials has opened new ways of producing engineered tissue substitutes. In this study, we investigated whether the therapeutic potential of an acellular porous scaffold made of type I collagen can be improved by the addition of a powerful trophic agent in the form of mesenchymal stromal cells conditioned medium (MSC‐CM) in order to be used as an acellular scaffold for skin wound healing treatment. Our experiments showed that MSC‐CM sustained the adherence of keratinocytes and fibroblasts as well as the proliferation of keratinocytes. Moreover, MSC‐CM had chemoattractant properties for keratinocytes and endothelial cells, attributable to the content of trophic and pro‐angiogenic factors. Also, for the dermal fibroblasts cultured on collagen scaffold in the presence of MSC‐CM versus serum control, the ratio between collagen III and I mRNAs increased by 2‐fold. Furthermore, the gene expression for α‐smooth muscle actin, tissue inhibitor of metalloproteinase‐1 and 2 and matrix metalloproteinase‐14 was significantly increased by approximately 2‐fold. In conclusion, factors existing in MSC‐CM improve the colonization of collagen 3D scaffolds, by sustaining the adherence and proliferation of keratinocytes and by inducing a pro‐healing phenotype in fibroblasts.